(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The project aims, the main advantage of Image Processing Based Fire Detection System is theearly warning benefit. This system can be installed just about anywhere in a commercial building, malls and at many more public places for fire detection. This system uses camera fordetecting fires. SO, we do not need any other sensors to detect fire. This system can be installed at any remote premise which has threat of fire accidents. Image processing is a type of processing in which the input image is transformed into another image as output with certain techniques applied to it System processes the camera input and then processor processes it to detect fires. The heat signatures and fire illumination patterns are detected in images to determine if it is a fire and take action accordingly. On detecting fire system goes into emergency mode and sounds an alarm. Also displays the status on the LCD display informing about the system. Raspberry Pi-based fire detection systems can be integrated with emergency services and first responders. The major advantages in this method are: sending the information to the person at any time, any place and remote monitoring for immediate actions.